2000
DOI: 10.4049/jimmunol.165.8.4685
|View full text |Cite
|
Sign up to set email alerts
|

Impaired CD4 T Cell Activation Due to Reliance Upon B Cell-Mediated Costimulation in Nonobese Diabetic (NOD) Mice

Abstract: Diabetes in nonobese diabetic (NOD) mice results from the activation of I-Ag7-restricted, islet-reactive T cells. This study delineates several characteristics of NOD CD4 T cell activation, which, independent of I-Ag7, are likely to promote a dysregulated state of peripheral T cell tolerance. NOD CD4 T cell activation was found to be resistant to antigenic stimulation via the TCR complex, using the progression of cell division as a measure. The extent of NOD CD4 T cell division was highly sensitive to changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 54 publications
4
67
2
Order By: Relevance
“…Although the exact role of B cell involvement is unclear, it is suggested that the antigenpresenting ability of B cells is critical in NOD-associated T cell activation [13][14][15] and selection of the diabetogenic T cell repertoire. CCR5 expression is not reported for B cells, but nearly all B cells from NOD mice showed elevated expression of this receptor (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact role of B cell involvement is unclear, it is suggested that the antigenpresenting ability of B cells is critical in NOD-associated T cell activation [13][14][15] and selection of the diabetogenic T cell repertoire. CCR5 expression is not reported for B cells, but nearly all B cells from NOD mice showed elevated expression of this receptor (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1). Although T cells from NOD mice transfer disease [11,12], B cells are also reported to have an important role in diabetes development and probably in antigen presentation in this context [13][14][15]. Lymphocyte CCR5 expression was similar in 4-month-old NOD mice (not shown).…”
Section: Activated T Cells In Nod Mice Express a Functional Ccr5 Recementioning
confidence: 99%
“…Using CFSE labeling, they found that NOD CD4 T cells responded less well to anti-CD3 stimulation compared with B6 CD4 T cells, a phenomenon related to the non-MHC genes in the NOD genetic background and not to the expression of the MHC haplotype [71]. Both B cell and non-B cell antigen-presenting cells were tested for their ability to effectively activate CD4 T cells.…”
Section: B Cell Characteristics In Nod Micementioning
confidence: 99%
“…In addition, NOD mice exhibit a large array of cellular and humoral immune abnormalities including defective macrophage and dendritic cell maturation (12,13), defects in CD4 ϩ T cell response to superantigens (14,15), low levels of NK and NKT cell activity (16 -19), and deficiencies in regulatory CD4…”
mentioning
confidence: 99%